2008
DOI: 10.1111/j.1360-0443.2007.02113.x
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic variations in tobacco consumption, intention to quit and self‐efficacy to quit among male smokers in Thailand and Malaysia: results from the International Tobacco Control–South‐East Asia (ITC–SEA) survey

Abstract: Aim To examine the association of socio-economic position (education, income and employment status) with cigarette consumption, intention to quit and self-efficacy to quit among male smokers in Thailand and Malaysia. Design and setting The data were based on a survey of adult smokers conducted in early 2005 in Thailand and Malaysia as part of the International Tobacco Control-South-East Asia (ITC-SEA) project. Participants A total of 1846 men in Thailand and 1906 men in Malaysia. Measurement Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
2

Year Published

2009
2009
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 11 publications
8
34
2
Order By: Relevance
“…Our study finding of education (primary/secondary) to be a significant predictor of quit attempts for smokers in disaggregated analysis as well as for tobacco users in combined analysis is aligned to similar findings reported from western countries (Hatziandreu et al, 1990;Lee and Kahende, 2000) and also South East Asia (Siahpush, 2008). However, in our study smokeless tobacco users did not show an influence of education which is similar to the European CEASE study (Monso, 2001) and ITC-South East Asia study on Malaysian sample (Siahpush et al, 2008) which did not find education to have a significant effect on outcome.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our study finding of education (primary/secondary) to be a significant predictor of quit attempts for smokers in disaggregated analysis as well as for tobacco users in combined analysis is aligned to similar findings reported from western countries (Hatziandreu et al, 1990;Lee and Kahende, 2000) and also South East Asia (Siahpush, 2008). However, in our study smokeless tobacco users did not show an influence of education which is similar to the European CEASE study (Monso, 2001) and ITC-South East Asia study on Malaysian sample (Siahpush et al, 2008) which did not find education to have a significant effect on outcome.…”
Section: Discussionsupporting
confidence: 75%
“…However, in our study smokeless tobacco users did not show an influence of education which is similar to the European CEASE study (Monso, 2001) and ITC-South East Asia study on Malaysian sample (Siahpush et al, 2008) which did not find education to have a significant effect on outcome. Our study found that higher socioeconomic status (SES) measured by monthly expenditure quintiles to be a significant determinant for quit attempts among both smokers as well as smokeless tobacco users, which is similar to the findings in previous studies (Hymowitz et al, 1997;Reid, 2010).…”
Section: Discussionsupporting
confidence: 65%
“…Better understanding of this topic may provide a clearer picture for the policy makers of the directions to design proper intervention strategies. To our knowledge, numerous studies have examined this issue in Malaysia (Siahpush et al, 2008;Lim et al, 2009;Tan et al, 2009;Al-Naggar and Saghir, 2011). However, they only focus on investigating the socio-demographic differences in smoking participation.…”
Section: Exploring Factors Influencing Smoking Behaviour In Malaysiamentioning
confidence: 99%
“…This knowledge from developed countries is not necessarily generalizable to developing countries, due to different socioeconomic conditions and cultural contexts as well as disparities in tobacco control policies and social acceptability of smoking (Abdullah & Husten, 2004;Siahpush, Borland, Yong, Kin, & Sirirassamee, 2008). Siahpush et al (2008) examined the association of socioeconomic position with cigarette consumption, intention to quit, and self-efficacy to quit among male smokers in Thailand and Malaysia using the ITC-Southeast Asia (SEA) survey.…”
Section: Introductionmentioning
confidence: 99%
“…Siahpush et al (2008) examined the association of socioeconomic position with cigarette consumption, intention to quit, and self-efficacy to quit among male smokers in Thailand and Malaysia using the ITC-Southeast Asia (SEA) survey. They found that in the Malaysian sample, higher level of education was not associated with intention to quit or selfefficacy to quit or cigarette consumption; in Thailand, higher level of education was associated strongly with not having selfefficacy, and higher income was not found to be associated with an intention to quit in either country.…”
Section: Introductionmentioning
confidence: 99%